Discussion Of Mining, Petroleum, And Coal Papers Presented At New York Meeting, February, 1922 (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1922)
CONTENTS PAGE Rae, Colin C.-A Possible Origin of Oil. Discussed by S. Linker, Colin C. Rae... 2 Cottingham, Kenneth.-Subsurface Conditions on Portion of Arches Fork Anticline. Discussed by David B. Reger 6 Moyer, W. Irwin.-Time to Pay Out as a Basis for Valuation of Oil Properties. Discussed by H. J. Smith 9 Pogue, Joseph E.-Future Demands on Oil Industry of United States. Discussed by James O. Lewis 11 J. J. Walsh.-Coa-lmine Ventilation. Discussed by W. B. Daly, J. J. Walsh, R. R. Sayers, H. H. Stock, George S. Rice, James W. Paul, D. Harrington, T. D. Thomas 15 Longyear, Robert Davis.-Diamond-drill Sampling Methods. Discussed by Ira B. Joralemon, J. J. Rutledge, E. C. Harder 19 Joralemon, Ira B.-Sampling and Estimating Disseminated Copper Deposits. Discussed by J. Parke Channing, John E. Hodge, E.E. Hunner, B. B. Gottsberger, W. Y. Westervelt, W. O. Hotchkiss 20 Boericke, W. F.-Sampling and Estimating Zinc and Lead Orebodies in Mississippi Valley. Discussed by J. Parke Channing, Arthur Thacher 24 Daly, W. B. and Linforth, F. A.-Organization of Mine Sampling at Anaconda. Discussed by George A. Packard, W. B. Daly, B. B. Gottsberger 25 Norris, E. M. and Rahilly, H. J.-Mine Fires. Discussed by R. Dawson Hall, W. B. Daly, Frank Haas, D. Harrington, Robert E. Tally 26 Raymond, R. M.-Safety Practice for Hoisting Ropes. Discussed by B. F. Tillson, Graham Bright, Rudolph Kudlich, J. F. Howe, Robert Peele, H. G. Davis. 30 Howe, J. F.-Use of Wire Rope in Mining Operations. Discussed by Horace F. Lunt, J. F. Howe, B. F. Tillson 36 Tanner, W. N., and Jaccard, F. C.-Wire Rope and Safety in Hoisting at Butte Mines. Discussed by Horace F. Lunt, W. B. Daly, C. L. Colburn, William Kelly, Robert Peele, B. F. Tillson, Graham Bright, Charles E. Locke 38 Richardson, A. S.-Ventilation of Butte Mines of Anaconda Copper Mining Co. Discussed by D. Harrington, Chas. A. Mitke 42 Stuart, Charles E.-Storage-battery Locomotive as Applied to Mine Haulage. Discussed by Howard N. Eavenson, Charles E. Stuart, William Kelly, Arthur Thacher, W. H. Patton, Graham Bright 45 Woodward, C. D.-Electric Haulage Systems in Butte Mines. Discussed by William Kelly, Graham Bright, Howard N. Eavenson, C. E. Arnold, Gerard B. Rosenblatt, K. A. Pauly 47 Harrington, D.-Efficient Ventilation of Metal Mines. Discussed by R. E. Simpson 52 Otagawa, Masayuki.-Mining Methods at the Ashio Copper Mine. Discussed by Horace V. Winchell, D. W. Brunton 52 Stoek, H. H. and Clagett, Thomas H.-Coal Mining Methods. Discussed by P. D. Browning, G. L. Cox, Erskine Ramsay, Frank Haas, George S. Rice.